Characterization of Freeze-Dried Strawberries (Fragaria x ananassa var. Mencir): Quality on Physical Information - Fallah, Annas Miftahul; Putri, Refika Melina; Yuliani, Wahyu; Wagiman, Wagiman; Falah, Mohammad Affan Fajar (Journal of Agri-Food Science and Technology, 2024)
Drying fruits has many advantages for consumers, such as allowing them to be consumed in various processes and products during all seasons. Freeze-dried strawberries (FDS) are an alternative for adding value to fresh strawberries, extending shelf life, and maintaining fresh fruit characteristics. The study contributed to determine the quality physical characteristics of FDS produced using osmotic dehydration (OD) combined with freeze-drying. A combination of FDSs production with three factors and levels, freezing times (4d, 14d, and 21d); OD solution concentrations (40°Brix, 50°Brix, and 60°Brix); cleavage times (initial, pre-OD, and post-OD); immersion times of 120 minutes; and lyophilization times of 24 hours were used to prepare FDS. The quality of physical information of FDSs was the color of the skinned fruit (L*a*b* and change of color (∆E)) and texture. The results of the study showed that the highest degree of L* and a* values were found in the combination of 14d, 50°Brix, post-OD; the lowest b* value was found in the combination of 21d, 40°Brix, initial split; the lowest ∆E value and the highest FDSs skin texture was found in the combination of 4d, 60°Brix, pre-OD. As an innovation, since no official Indonesian National Standard (SNI) is used as a reference for producing FDS, the research contributes to making good FDS products.